Pengaruh Kompensasi, Gaya Kepemimpinan, dan Kepuasan Kerja Terhadap Kinerja Karyawan - Indah Nuryanti; Beni Suhendra Winarso (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Every company has goals to achieve, such as improving product quality, increasing profits, and improving company performance. The achievement of these goals can be reflected by seeing the optimum level of employee performance achieved. To get optimal performance, the company needs to pay attention to factors that can influence the level of employee performance, such as compensation factors, leadership style, and job satisfaction. Therefore, the purpose of this study was to know and analyze the influence of compensation, leadership style, and job satisfaction on employee performance. The population in this study were all employees at PT Lembimjar Neutron Yogyakarta, then using a simple random sampling technique, 30 respondents were taken as research samples. The results of the questionnaire distribution data were then processed using the IBM SPSS Statistics 23, with the analysis techniques used being regression test, coefficient of determination, and hypothesis test. The results of this study provide that job satisfaction has a significant influence on employee performance. However, the compensation and leadership style applied in the company did not influence employee performance at PT Lembimjar Neutron Yogyakarta.